Media w Rosji a wojna informacyjna. Analiza zjawiska na przykładzie programu „Wiesti o 20:00” w czasie konfliktu wojennego na wschodzie Ukrainy - Onishechko, Yaryna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The purpose of this paper is to discuss issues related to the use of media as a tool of information warfare: analysis of randomly selected episodes of the Russia-1 headline news show in terms of publications related to the conflict in the eastern Ukraine. Russia was selected, because of the fact that its mass media for many years have been engaged in shaping anti Ukrainian attitudes not only within their own country but also abroad. The importance of information has changed. Some time ago, it was a tool supporting the implementation of active military operations, but now it could be used as a main force, which sets the direction and determines the effects of the war. This paper attempts to answer the question of what role the Russian state television plays in conducting information warfare against Ukraine, supporting military operations in the east of the country. The object of the study was the Russian state television, namely the headline news show, summarizing the day called “Vesti at 20:00” in the period from 14 July 2014 until 14 May 2015.